A Hybrid Cut-Off Point AHP-TOPSIS Framework for Raw Material Supplier Selection in the Digital Printing Industry - Yayan Saputra (Blend Sains Jurnal Teknik, 2026)
Raw material supplier selection is a strategic decision that influences production continuity, operational efficiency, and product quality, particularly in the digital printing industry, which is inherently time-sensitive. In practice, supplier selection processes are often based primarily on partial considerations of price and quality, which may lead to delivery delays, mismatches in supply quantity, and inconsistencies in material quality. This study aims to develop a hybrid decision-making framework integrating the Cut-Off Point method, Analytical Hierarchy Process (AHP), and Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) to support systematic and data-driven raw material supplier selection. The initial stage employs the Cut-Off Point method combined with Focus Group Discussion (FGD) to identify relevant evaluation criteria, resulting in five main criteria and twenty subcriteria. The AHP method is applied to determine criteria weights with consistency testing, while TOPSIS is used to rank supplier alternatives based on their relative closeness to the ideal solution. A case study was conducted in a digital printing manufacturing company using real operational data from 2025. The results indicate that delivery is the most influential criterion with a weight of 0.42, where delivery punctuality emerges as the most dominant subcriterion with a weight of 0.50. TOPSIS analysis shows that supplier PT. C achieves the highest preference value of 0.5843 and is therefore prioritized as the best supplier. The proposed hybrid framework enhances the objectivity of supplier selection processes and provides managerial implications for improving raw material supply reliability in the digital printing industry.